Modified kinetics and selectivity of sodium channels in frog skeletal muscle fibers treated with aconitine (The Rockefeller University Press, 1982)
The effect of the plant alkaloid aconitine on sodium channel kinetics, ionic selectivity, and blockage by protons and tetrodotoxin (TTX) has been studied in frog skeletal muscle. Treatment with 0.25 or 0.3 mM aconitine alters sodium channels so that the threshold of activation is shifted 40-50 mV in the hyperpolarized direction. In contrast to previous results in frog nerve, inactivation is complete for depolarizations beyond about -60 mV. After aconitine treatment, the steady state level of inactivation is shifted approximately 20 mV in the hyperpolarizing direction. Concomitant with changes in channel kinetics, the relative permeability of the sodium channel to NH4,K, and Cs is increased. This altered selectivity is not accompanied by altered block by protons or TTX. The results suggest that sites other than those involved in channel block by protons and TTX are important in determining sodium channel selectivity.